Magnitude of Neonatal Sepsis and Factors Associated with It among Neonates Admitted to the Intensive Care Units of Neonate in the Primary Hospital of Hawzen, Tigray, Ethiopia, 2020 - Fre Gebremeskel; Haftay Gebremedhin; Medhin Mehari (Global Health, Epidemiology and Genomics)
Purpose. Neonatal sepsis contributes substantially to neonatal mortality and morbidity and is an ongoing major global public health problem particularly in developing countries. A significant proportion of mothers give birth in primary health care, but studies regarding neonatal sepsis and its associated factors among admitted neonates are limited to the hospital which may not be generalized to the primary health care unit. Therefore, this study aimed to assess the proportion of neonatal sepsis and associated factors in the study areas. Objective. To assess the magnitude of neonatal sepsis and its associated factors among neonates admitted to Neonatal Intensive Care Units (NICUs) of Hawzen Primary Hospital, Eastern Zone, Tigray, North Ethiopia, 2020. Methods. An institution-based cross-sectional study design was carried out among 290 study participants in Hawzen Primary Hospital in January–March/2020. A systematic random sampling method was applied to select the study participants, and pretested and structured questionnaires were used to collect data. The collected data were coded, entered, cleaned, and analyzed using SPSS version 20.0 software. Binary logistic regression analyses with a confidence interval of 95% were used to select determinant factors. Statistically significant factors were identified using the adjusted odds ratio (AOR). Statistical significance was determined at p value <0.05. Binary and multivariable logistic regression analyses were applied to see the association of the variables at a p<0.05. Results. In this study, the overall proportion of neonatal sepsis was (60.2%) 95% CI (56, 68)]. Birth asphyxia [AOR = 2.04; 95%CI (1.07, 3.93)], maternal age of 15–19 [AOR = 2.00; 95% CI (1.81, 11.93)], duration of labor greater or equal to 24 hours [AOR = 3.00; 95% CI (2.67, 14.21)], history of oxygen administration [AOR = 2.37; 95% CI (1.18, 4.75)], neonatal age of greater or equal to seven days [AOR = 4.0595% CI (1.07, 3.93), and home delivery [AOR = 5.00; 95% CI (2.34, 18.92)] were the predictor variables for neonatal sepsis. Conclusion. In this study, neonatal sepsis was high. Birth asphyxia, intranasal oxygen administration, age of the mother, home delivery, and duration of labor were associated with neonatal sepsis.